2004
DOI: 10.1007/s10750-004-4948-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent patterns of sediment accumulation in a small closed eutrophic lake revealed by the sediment records

Abstract: A short-core palaeolimnological investigation was undertaken with the aim of acquiring knowledge of sediment deposition. Analyses of the lithological composition of sediments from the whole-lake basin were performed on the small eutrophic L. Linaja¨rv (northern Estonia) and the concentrations of mineral and organic matter were measured on 647 sub-samples from 14 sediment cores. The accumulation rate of the sediment sequences was established and C/N ratios of organic matter in some cores were recorded. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…A large amount of material was brought into the lake and later re-deposited in the steep slope area, where the inclination is more than 14% (Fig. 2b) or at sites with greater exposition to the prevailing wind directions (Punning et al, 2004). This may cause also redeposition of macrofossils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large amount of material was brought into the lake and later re-deposited in the steep slope area, where the inclination is more than 14% (Fig. 2b) or at sites with greater exposition to the prevailing wind directions (Punning et al, 2004). This may cause also redeposition of macrofossils.…”
Section: Discussionmentioning
confidence: 99%
“…The northern part of the lake is shallow with a mean depth of 1-2 m. It forms a relatively separate system from which matter fluxes to other parts of the lake are apparently not very large (Punning et al, 2004). The smallest slope inclinations in the south-western part of L. Viitna occur at depths of 4-5 m (Fig.…”
Section: Study Sitesmentioning
confidence: 98%
“…Comparison of the fluctuations in the water level in some Estonian lakes with the lithological composition of the sediment, P content, carbon and nitrogen ratio, fossil pigments and diatom communities showed that in medium-term time scale (10 3 years) the decisive factor in the trophy of the lake was the depth of the water column above the sediment (Punning et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Less attention has been paid to sedimentary processes, especially to the grain size of lake sediments; however, these studies have been promising in investigating lake-level variations in small temperate lakes (Digerfeldt, 1986;Punning, Alliksaar, Terasmaa, & Jevrejeva, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…BP). Punning et al (2004) demonstrated that this ratio is useful for indicating periods of stability (low value) and instability (high value) in the sedimentary regime of a lake.…”
Section: Sedimentological Indicatorsmentioning
confidence: 99%